2020
DOI: 10.1093/rheumatology/keaa064
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and neonatal outcomes associated with biologic exposure before and during pregnancy in women with inflammatory systemic diseases: a systematic review and meta-analysis of observational studies

Abstract: Objective To determine the association between exposure to biologics in pregnant women with inflammatory systemic diseases and maternal and neonatal outcomes through a meta-analysis of findings from studies identified in a systematic review. Methods We conducted a systematic review of Medline, Embase, and Cochrane Database of Systematic Reviews to identify observational studies assessing the perinatal impacts of biologic in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 32 publications
3
34
0
4
Order By: Relevance
“…Regarding the association of CMs, preterm birth, and birth weight with biologic use during pregnancy, a recent meta-analysis by Tsao et al also showed no increased odds ratios [11]. Nonetheless, it should be considered that the methods in the two studies are different.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the association of CMs, preterm birth, and birth weight with biologic use during pregnancy, a recent meta-analysis by Tsao et al also showed no increased odds ratios [11]. Nonetheless, it should be considered that the methods in the two studies are different.…”
Section: Discussionmentioning
confidence: 99%
“…A PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) [ 11 ] guideline was followed in the design of this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…• Immunosuppressive Agents: Along with corticosteroids, other immunosuppressive agents form the mainstay of treatment of initial attacks and relapses. Azathioprine is a relatively safe option for use during pregnancy and lactation (49,61), despite indications of a slightly increased risk of adverse outcomes, and should be initiated or continued, regardless of gestational age, should the clinical condition require pharmacologic management (62,63). Tacrolimus has been used effectively, but is not among the first line treatments approved for NMOSD.…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal antibodies: are being increasingly used in pregnancy. A recent systematic review of systemic autoimmune conditions showed that there is no association between their use during pregnancy and the risk of congenital anomalies or preterm deliveries compared with disease matched unexposed pregnant women ( 64 ). Owing to their high molecular weight, only small amounts are likely to be transferred into breast milk.…”
Section: Discussionmentioning
confidence: 99%